Effects of long-term metal exposure on the structure and co-occurrence patterns of the oral microbiota of residents around a mining area - Pei, Shuwei; Feng, Lu; Zhang, Yonghua; Liu, Jiangyun; Li, Jia; Zheng, Qiwen; Liu, Xingrong; Luo, Bin; Ruan, Ye; Li, Huan; Hu, Weigang; Niu, Jingping; et al. (Frontiers in Microbiology, 2023)
Objectives The aim of our study was to investigate the impact of long-term exposure to heavy metals on the microbiome of the buccal mucosa, to unveil the link between environmental contamination and the oral microbial ecosystem, and to comprehend its potential health implications. Methods Subjects were divided into two groups: the exposure group and the control group. We collected samples of buccal mucosa, soil, and blood, and conducted microbial diversity analysis on both groups of oral samples using 16S rRNA gene sequencing. The concentrations of heavy metals in blood and soil samples were also determined. Additionally, microbial networks were constructed for the purpose of topological analysis. Results Due to long-term exposure to heavy metals, the relative abundance of Rhodococcus, Delftia, Fusobacterium, and Peptostreptococcus increased, while the abundance of Streptococcus, Gemella, Prevotella, Granulicatella, and Porphyromonas decreased. The concentrations of heavy metals in the blood (Pb, Cd, Hg, and Mo) were associated with the growth of Rhodococcus, Delftia, Porphyromonas, and Gemella. In addition, the relative abundances of some pathogenic bacteria, such as Streptococcus anginosus, S. gordonii, and S. mutans, were found to be enriched in the exposure group. Compared to the exposure group network, the control group network had a greater number of nodes, modules, interactive species, and keystone taxa. Module hubs and connectors in the control group converted into peripherals in the exposure group, indicating that keystone taxa changed. Metals in the blood (Pb, Cd, Hg, and Mo) were drivers of the microbial network of the buccal mucosa, which can have adverse effects on the network, thus providing conditions for the occurrence of certain diseases. Conclusion Long-term exposure to multiple metals perturbs normal bacterial communities in the buccal mucosa of residents in contaminated areas. This exposure reduces the complexity and stability of the microbial network and increases the risk of developing various diseases.